2020
DOI: 10.21203/rs.3.rs-111265/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulmonary Dysfunction in Patients Recovered from COVID-19 Pneumonia: A 6-Month Follow-up Study

Abstract: Objectives: This study investigates the clinical features and pulmonary functions of COVID-19 pneumonia survivors at 3 or 6 months after diagnosis in the Heilongjiang Province, China.Methods: Forty-six patients with COVID-19 pneumonia diagnosed since February 2020 were enrolled in this study for follow-up in July 2020. These patients were categorized into three groups: Group A (n=24) and Group B (n=11) who were diagnosed with moderate or severe pneumonia and followed up at three months after diagnosis; Group C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Thirty-six studies from 15 different countries reported respiratory complications among COVID-19 survivors. [ 11–14 , 16 , 19 , 20 , 22 , 24 , 26–28 , 31–33 , 36–38 , 40–42 , 44 , 45 , 47–49 , 51 , 54 , 55 , 58 , 59 , 67 , 69 , 72 , 74 , 75 ] Around 1778 patients suffered from respiratory complications after their recovery, which ranged from breathlessness to changes in pulmonary function. Out of this number, almost 581 patients had required oxygen supply and 237 had invasive or non-invasive ventilation during their infection.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six studies from 15 different countries reported respiratory complications among COVID-19 survivors. [ 11–14 , 16 , 19 , 20 , 22 , 24 , 26–28 , 31–33 , 36–38 , 40–42 , 44 , 45 , 47–49 , 51 , 54 , 55 , 58 , 59 , 67 , 69 , 72 , 74 , 75 ] Around 1778 patients suffered from respiratory complications after their recovery, which ranged from breathlessness to changes in pulmonary function. Out of this number, almost 581 patients had required oxygen supply and 237 had invasive or non-invasive ventilation during their infection.…”
Section: Resultsmentioning
confidence: 99%
“…Persisting symptoms with subsequent progression to poor functional status have been reported in a substantial proportion of COVID-19 survivors. 14,15 Pulmonary function impairment 16 , mental health problems, 17 and reduced quality of life 18 to a various extent have been reported in COVID-19 patients. These factors could have a long term impact on physical, mental, social and cognitive health and well being of COVID-19 infected patients, causing a decline in functional status.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in diffusion capacity for carbon monoxide (DLCO) and TLC were detected among COVID-19 survivors. Thus, they demonstrated the abnormal parenchymal diffusion that persisted in some recovered patients for up to 6 months post infection 44 . In addition, reduction in lung function based on FEV1 measurements may prove the restrictive lung disease that persisted in COVID-19 survivors 35 .…”
Section: Discussionmentioning
confidence: 94%
“…In a British study , 60% of the survivors had reported some persistent abnormalities in the lung parenchyma through lung magnetic resonance imaging (MRI) at 2-3 months post discharge 35 . Furthermore, abnormal FEV1 (<80%) or FEV1/FVC < 70% , MEF 50, MEF 25, MMEF 75/25 were presented in 52.17%, 72.73% ,and 45.45% of cases who had previously moderate/sever COVID-19 44 .…”
Section: Respiratory Sequelaementioning
confidence: 96%
See 1 more Smart Citation